Addressing recent challenges in isotope ratio mass spectrometry: Development of a method applicable to 1‐androstene‐steroids, 6α‐hydroxy‐androstenedione, and androstatrienedione. Issue 11 (31st August 2022) - Piper, Thomas; Thevis, Mario
Abstract: In 2020, the confirmation of the non‐endogenous origin of several pseudo‐endogenous steroids by means of isotope ratio mass spectrometry (IRMS) was recommended by the World Anti‐Doping Agency (WADA), in addition to previously established target analytes for IRMS in sports drug testing. To date, however, IRMS‐based methods validated in accordance with current WADA regulations have not been available. Therefore, the aim of this research project was the development and validation of a method to determine the carbon isotope ratios (CIR) of all newly considered pseudo‐endogenous steroids, encompassing the anabolic androgenic steroids comprising a 1‐ene‐core structure (5α‐androst‐1‐ene‐3β, 17β‐diol, 5α‐androst‐1‐ene‐3, 17‐dione [1AD], 17β‐hydroxy‐5α‐androst‐1‐en‐3‐one, 3α‐hydroxy‐5α‐androst‐1‐ene‐17‐one [1AND], and 3β‐hydroxy‐5α‐androst‐1‐ene‐17‐one [1EpiAND]), as well as steroids referred to as hormone and metabolic modulators (androsta‐1, 4, 6‐triene‐3, 17‐dione [TRD] and its main metabolite 17β‐hydroxy‐androsta‐1, 4, 6‐triene‐3‐one) and 6α‐ and 6β‐hydroxy‐androst‐4‐ene‐3, 17‐dione. With peak purity of target analytes being critical for IRMS analyses, a twofold high‐performance liquid chromatography (HPLC)‐based sample purification was employed, with all analytes being acetylated between the first and second HPLC fractionation. Using established gas chromatography/combustion/IRMS instrumentation, limits of quantification were estimated at 10 ng/ml for a 20 ml urine aliquot for all analytes, except for 1AND (20 ng/ml), and combined measurement uncertainties were estimated between 0.4‰ and 0.9‰. For proof‐of‐concept, samples collected after the single oral administration of a nutritional supplement containing 1AD and 1EpiAND were analyzed as well as existing excretion study urine samples obtained after the administration of 4‐androstenedione and TRD. Based on the obtained results, the developed method was considered to be fit‐for‐purpose. Abstract : A method to determine the carbon isotope ratios of nine potentially pseudo‐endogenous steroids relevant to sports drug testing was developed and validated. Using established gas chromatography/combustion/isotope ratio mass spectrometry instrumentation, limits of quantification were determined at 10 ng/ml for a 20 ml urine aliquot for all analytes, except for 1AND (20 ng/ml), and combined measurement uncertainties were found between 0.4‰ and 0.9‰.